Analisis Sistem Biaya Pemeliharaan (Mu’nah) dalam Pembiayaan Amanah (Studi Kasus Pegadaian Syariah Unit Bone) - Hasrika, Hasrika; Muis, Musrini (Islamic Banking and Finance, 2023)
This research discusses the Analysis of Maintenance Cost System (Mu'nah) in Amanah Financing at Pegadaian Sharia Unit Bone. The study aims to determine how the maintenance cost system (Mu'nah) works in Amanah financing at Pegadaian Sharia Unit Bone, the mechanism of Amanah financing products at Pegadaian Sharia Unit Bone, and the advantages and disadvantages of maintenance costs (Mu'nah) in Amanah financing at Pegadaian Sharia Unit Bone. The research employed a field research design with a qualitative approach. Primary and secondary data sources were utilized. The results of the research indicate that (1) the maintenance cost system (Mu'nah) in Amanah financing at Pegadaian Sharia Unit Bone is a maintenance cost (1%) multiplied by the vehicle price, with the vehicle's BPKB serving as collateral, as per the Fatwa DSN-MUI Number 688/DSN-MUI/III/2008. (2) The mechanism of Amanah financing products at Pegadaian Sharia Unit Bone involves document completion, analysis stages (survey and BI Checking system checks), signing and delivery of the DP, disbursement, payment to the dealer, delivery of the vehicle to prospective customers, and collateral goods to murtahīn, while still paying attention to elements of trust, agreement, duration, and risk to avoid undesirable situations. (3) The advantages and disadvantages of maintenance costs (Mu'nah) in Amanah financing at Pegadaian Sharia Unit Bone include delayed payments, inventory at the dealer, and surveys.